Crecimiento y composición bromatológica del molusco Pomacea maculata (Ampullariidae) utilizando un alimento natural y tres artificiales - Amasifuen Chumbe, Cesar Alberto (2024)
The present study evaluated the effect of three artificial diets and one natural diet on growth and bromatological composition of Pomacea maculata. The study was conducted in the UNAP fund of the city of San Lorenzo, province of Datem del Marañón (Loreto, Peru), from August to November 2022. A total of 240 captive-born P. maculata individuals were housed in 12 cages from 0.2m3 to a density of 20 individuals/cages. 4 treatments, 3 artificial diets (T1, T2 and T3) and 1 natural diet (T4), with three repetitions, distributed in a completely randomized design, were evaluated. The artificial foods were formulated on the basis of vegetable flours, eggshell flour, vitamin supplements, salt and oil; while the natural food was based on leaves of Xanthosoma sp. Every 15 days the weight and total length of the specimens were recorded. Zootechnical indices, cost of 1kg of churro produced and percentage of protein in the muscles were determined. At the end of the study significant differences (p0.05). The natural diet decreased the cost of producing 1kg of P. maculata (13.32 soles) and generated a slight increase in the percentage of protein in the P. maculata muscles, compared to the artificial diets. It is concluded that the churro Pomacea maculata adapts to the artificial T3 diet, which increases its weight growth and improves zootechnical indices (daily weight gain, specific growth rate and apparent feed conversion index).